Parallel Investigation As An Effective Step In Handling Cases Of Money Laundering Crimes Arising From Forestry And Environmental Crimes - Paklioy, Ronny Putra Dirgantara; Sopacua, Margie Gladies (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2023)
Introduction: Parallel Investigation, is a concept in the enforcement of money laundering or money laundering, in Law Number 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering or hereinafter referred to as the Anti-Money Laundering Law Article 74 stipulates that "The ML investigation is carried out by investigators predicate offense in accordance with the provisions of the procedural law and the provisions of laws and regulations, unless otherwise provided for by this law”. Money laundering is a further crime from the predicate crime, one of the predicate crimes that has a high risk of money laundering is forestry and environmental crimes, the provisions of the Anti-Money Laundering Law article 74 and the issuance of the Constitutional Court decision Number 15/PUU-XIX/2021, which applies the principle of parallel investigation in money laundering originating from forestry and environmental crimes.Purposes of the Research: The purpose of this study is to find out the effectiveness of using the principle of parallel investigation in handling money laundering offenses originating from forestry and environmental crimes.Results of the Research: The results of the study show that Parallel Investigation is an effective step in handling money laundering offenses arising from forestry and environmental crimes because Parallel investigation is a concept where investigators of predicate crimes, namely PPNS, can handle money laundering offenses investigations if there are findings in the investigation of predicate crimes, which will reduce the total costs. and it will not take a long time because there is no longer a need for a new investigation by combining ML investigations and forestry and environmental crimes into a single investigation process.